Examining the Effect of Budgetary Controls on the Financial Performance of Oman Telecommunication Company. - AL Mahroqi, Raya Mohammed (Advances in Social Sciences Research Journal, 2021)
The budgeting process and budgetary control are one of the most important activities that have great importance in the techniques used for planning and monitoring activities and all the administrative and financial functions of the organization. This study aims to assess the effect of budgetary control on the financial performance of the Oman Telecommunications Company and verify the effectiveness of budgetary control techniques in the company, in light of the support and role of top management for budgetary control techniques in the company. This study will allow financial managers in various companies to understand the nature of the work of budgetary control techniques, their importance, and the extent of the impact of each technique, and thus managers will be able to determine the best-used and appropriate techniques that will lead to raising efficiency in financial and organizational performance. As for the research methodology used in the study, the survey method based on questionnaires and interviews was used. Data were analyzed using frequency distribution, correlations, and regression analysis. Microsoft Excel was used to analyze the collected data. As for the interview, they were analyzed by descriptive and explanatory methods. The results indicated that there is a positive relationship between budgetary control and the financial performance of the company, the differential impact of budgetary control techniques, and the confirmation of the company’s use of the technique of variance analysis and accounting responsibility, as well as the importance of budgetary control procedures. The results also indicate the importance of support and the role of top management for budgetary control techniques. Several recommendations were made through the results of this study. The recommendation was made on the need to understand and implement the company’s adjustment of funds technique for its importance in improving and raising the company’s financial performance significantly in the company. Keywords: Budgetary Control, Organizational Financial Performance, Budgetary Control Techniques, Budgeting